Polymorphic scent gland secretions in Nelima harvestmen: “Sclerosomatid compounds” but different chemical lineages - Raspotnig, Günther; Hüfner, Antje; Bodner, Michaela; Blesl, Julia; Schaider, Miriam; Escalante, Ignacio; Kunert, Olaf (Frontiers in Ecology and Evolution, 2022)
The scent glands of harvestmen (Opiliones) produce secretions of taxon-specific composition. One class of compounds, assumed to be a key group in opilionid chemosystematics and prevalent among sclerosomatid Eupnoi, was termed “sclerosomatid compounds” (SCs). Known compounds of this group comprise acyclic 4-methyl-branched ethyl-ketones and -alcohols as well as 2,4-dimethyl-branched primary alcohols and aldehydes, originally described from several species of North American Leiobuninae. We analyzed the scent gland secretions of Nelima ssp. (Sclerosomatidae, Leiobuninae) from two continents by gas chromatography-mass spectrometry, NMR, stereoselective synthesis, and chiral chromatography. We found a surprising chemical dichotomy: While North American N. paesserli produced typical acyclic SCs such as (E)-4-methyl-4-hexen-3-one, the secretions of European Nelima-species exhibited a mixture of aromatic and aliphatic compounds, namely (R)-2-methyl-1-phenyl-pentan-3-one (MPP), 4-phenyl-2-butanone (PB), 2-phenylacetamide (PA) as well as (2R,4R)-2,4-dimethylhexanoic acid (DHA), all of which are new for the secretion pool of harvestmen. Remarkably, in N. sempronii, the secretions of juveniles (containing PB) differed from the secretions of adults (containing MPP and DHA). Though the chemistry of European Nelima clearly diverged at first sight, all compounds detected either possess specific chemical motifs that allow an assignment to the class of SCs or appear to be biochemically/ontogenetically connected to SC-components. Thus, we here add novel compounds to the pool of SCs along with an extension of the definition of SCs to include aromatic compounds with SC-motifs. Furthermore, we describe a first case of juvenile-adult polymorphism for the exocrine secretions of harvestmen and provide a scheme of how secretions are regenerated.